Influence of humic preparations on the efficiency of vegetable crops protection against diseases - Borzykh, O.; Serhienko, V.; Tkalenko, H.; Shyta, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. To investigate the effect of humic preparations on the efficiency of vegetable crops protection against diseases.Methods. Informational and analytical (collection of materials and analysis of literary sources), field research (setting up experiments, monitoring of plant development, assessment, harvesting), mathematical and statistical (processing of research results). Humic preparations used vere Gumifield, w.g. (potassium salt of humic acids, 720 g/ kg), and Fulvital plus, WP (fulvic acids, 200 g/kg + microelements, 75 g/ kg) were used separately and in mixtures with fungicides for spraying plants during vegetation period. Experiments were conducted on cucumbers, tomatoes, white cabbage.Results. During the years of research downy mildew dominated on cucumber and dry spot or alternaria — on tomato and white cabbage crops. Humic preparations, when applied separately, restrained the development of diseases on tomatoes at the level of 59—64%, on cucumbers — at the level of 46—69%. The protective effect was much higher when mixtures of humates with fungicides were used. Combined application of preparations Gumifield, w.g., 100 g/ha with Ridomil Gold MC 68 WG, w.g. (Metalaxyl-M, 40 g/ kg + mancozeb, 640 g/kg), 2 kg/ha and Fulvital plus, WP 150 g/ ha with Ridomil Gold MC 68 WG, w.g., 2 kg/ha on tomatoes ensured efficiency on average level of 70.6 and 73.5% respectively. Application of mixtures Gumifield, w.g., 100 g/ha with Acrobat MC, w.g. (dimethomorph, 90 g/ kg + mancozeb, 600 g/ kg), 1.5 kg/ha and Fulvital plus, WP 150 g/ha with Acrobat MC, w.g., 1.5 kg/ha on cucumbers ensured efficiency at level of 74.7% and 75.2%. On white cabbage the efficiency of mixtures of Rovral Aquaflo, SC (iprodione, 500 g/l), 1 l/ha with Gumifield, w.g. 100 g/ ha and Rovral Aquaflo, SC, 1 l/ha + Fulvital plus, WP 150 g/ ha was on average 70.8% and 77.4%, respectively. These results were close to or exceeded the protective effect of fungicides at full application rates. The use of humic preparations contributed to the increase in the yield of crops. The yield increase on various crops was from 10 to 21%.Conclusions. Humic preparations have a positive effect on the growth, development and productivity of vegetable crops. The use of humic preparations alone and in mixtures with fungicides significantly limits damage to plants by diseases during the growing season and increases the yield of crops. The protective effect of humic preparations in mixtures with fungicides with reduced rates was at the level of fungicides with full rates. Due to the use of humic preparations, the pesticide load on the agrocenosis is reduced and the safety of vegetable products is increased.